Concepções de leitura sob a ótica de docentes de Língua Portuguesa do ensino fundamental : anos finais - Santos, Ana Patrícia dos (2021)
This paper is linked to the Research Group Alphabetization and School Literacy (ALFALE), of the Postgraduate Program in Education, of the Human and Social Sciences Institute, of the Federal University of Mato Grosso (UFMT) – University Campus of Rondonópolis (PPGEdu/ICHS/UFMT/CUR), in the research line: Languages, Culture and Knowledge Construction: historical and contemporary perspectives. The present study stems from the challenges experienced by me since my personal development, especially in relation to reading, up to my career path, as teacher and pedagogical coordinator, main reason that made me search for theoretical paths and of investigation that better lead my teaching practice. From this assumption, the research arose from the following inquiries: How do the Portuguese Language teachers of the Primary Level-Final Grades of the State School Carlos Pereira Barbosa, in Rondonópolis/MT, work with reading in the classroom? And, what reading concepts are assumed by these teachers when they record their classes? In face of such questionings, the general objective of the research was outlined in the sense of comprehending, from the narratives of the participants of the research and their written records, what are the reading concepts that guide the pedagogical work of these teachers of Portuguese Language of the Primary Level - Final Years, in addition to reflecting if the theoretical perspective adopted by them has contributed to the work with reading. In order to meet this purpose, the theoretical ground stemmed from authors like, Bakhtin (1997, 2016); Volóchinov (2018), Geraldi (2011), Kleiman (1993, 2000), Koch and Elias (2012, 2013), Ângelo and Menegassi (2010), Perfeito (2005) among other papers. As methodology, autobiographical and document research were used, with qualitative support, which involved as starting point of the personal and professional narrative of the researcher, showing where the interest for the study emerged and also, the narratives of three teachers of Portuguese Language of the locus school, who reported their experiences on reading along their life journey. The interpretative analysis, based on Bortoni-Ricardo (2008), sustained some reflections, among them the ones that the records of the teachers need to be more detailed, in order to make it clear how the activities related to the practice of reading occurred. Another important question of the study, was the verification that the participants of the research approached practices of reading that sometimes had the focus on the reader, other times on the author and others on the text, but on the notes taken about the work developed in the classroom there was no sign of interaction between these elements. Concerning the instructions for the readings used by the teachers, it was observed some conceptual mistakes about the ways of reading like the shared reading and with protocol pauses. Therefore, from these gatherings, it was determined the need of the teacher in renewing some theoretical guidelines, mainly about the teaching of reading with the intention of developing with their students practices that consider the context of the classroom.